Law No. 175 of the year 2022 Amending Some Provisions of the Law on the Protection of Competition and Prevention of Monopolistic Practices Promulgated by Law No. 3 of the year 2005 = قانون رقم 175 لسنة 2022 بتعديل بعض أحكام قانون حماية المنافسة ومنع الممارسات الاحتكارية الصادر بالقانون رقم 3 لسنة 2005 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic